Prognosis of Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The value of standard and ambulatory electroencephalography in the prediction of continuing neonatal seizures was investigated in the Department of Neurology, State University of New York, Buffalo, NY.